Một số công cụ chứng khoán phái sinh và khả năng phát triển ở Việt Nam - Nguyễn, Ngô Tuấn (2011)
Tác giả: Nguyễn Ngô Tuấn, CN; Nguyễn Thị Thanh Hương, CN; Dương Mạnh Hùng, CN; Nguyễn Mạnh Huyền, CN; Nguyễn Thúy Lan, CN; Nguyễn Đức Huấn, CN -- Từ khóa: Chứng khoán; Chứng khoán phái sinh